2003
DOI: 10.1104/pp.102.016188
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of CONSTANS-Like Gene Families in Barley, Rice, and Arabidopsis

Abstract: The CO (CONSTANS) gene of Arabidopsis has an important role in the regulation of flowering by photoperiod. CO is part of a gene family with 17 members that are subdivided into three classes, termed Group I to III here. All members of the family have a CCT (CO, CO-like, TOC1) domain near the carboxy terminus. Group I genes, which include CO, have two zinc finger B-boxes near the amino terminus. Group II genes have one B-box, and Group III genes have one B-box and a second diverged zinc finger. Analysis of rice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
535
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(561 citation statements)
references
References 45 publications
24
535
0
2
Order By: Relevance
“…Equally unclear is the link between the CONSTANS family of transcription factors and PCD. The CONSTANS genes in Arabidopsis have an important role in the regulation of flowering by photoperiod [39,40]. A recent analysis of H 2 O 2 -induced cell death gene expression in tobacco also identified WRKY, NAM and MYB transcription factors as among the earliest genes induced [41].…”
Section: Transcription Factors and The Global Transcriptional Reprogrmentioning
confidence: 99%
“…Equally unclear is the link between the CONSTANS family of transcription factors and PCD. The CONSTANS genes in Arabidopsis have an important role in the regulation of flowering by photoperiod [39,40]. A recent analysis of H 2 O 2 -induced cell death gene expression in tobacco also identified WRKY, NAM and MYB transcription factors as among the earliest genes induced [41].…”
Section: Transcription Factors and The Global Transcriptional Reprogrmentioning
confidence: 99%
“…Comparison of the CCT domains of these three sequences with the CCT domains from other grass genes (Griffiths et al 2003) demonstrated that ZCCT-Hc belongs to the ZCCT group ( Figure 5). Inclusion of ZCCT-Hc within the ZCCT cluster was confirmed using alternative clustering methods (Kumar et al 2001): UPGMA ( Figure 5), Neighbor Joining, Minimum Evolution and Maximum parsimony (data not shown).…”
Section: Cloning Of Zcct-hcmentioning
confidence: 99%
“…In barley, within the dominant Vrn-H1 class, we found no significant differences in flowering time between the plants carrying the recessive vrn-H2 or the dominant Vrn-H2 alleles. On the (Griffiths et al 2003). Os = Oryza sativa, Hv = Hordeum vulgare, Tm = Triticum monococcum.…”
Section: Barley Vrn Loci and Their Epistatic Interactionsmentioning
confidence: 99%
“…SALT TOLERANCE (STO) is a B-box type zinc finger protein with sequence similarities to CONSTANS [13]. It is also called BBX24 according to the nomenclature for the B-box transcription factors [14], and we use this nomenclature in the rest of the paper.…”
Section: Introductionmentioning
confidence: 99%